A positive electrode material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611247970.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]然而,上述方案在实际应用中仍存在一些不足
[0036]本发明通过将电压敏感材料直接构建为包覆于磷酸铁锂内核表面的中间层,由过充电压直接触发氧化产气,省去了现有方案中依赖活化剂激发产气的中间环节,从根本上消除了产气响应的固有延迟,使得气体能够在电池温度急剧上升至危险水平之前快速积累并触发防爆阀,显著提升了过充安全保护的及时性和可靠性;同时,外壳层采用快离子导体材料构成的多孔结构,在保证锂离子正常传输和气体顺畅释放的同时,有效隔离了中间层与电解液,避免了对电池倍率性能和循环寿命的不利影响,从而实现了电池常规电化学性能与过充安全性之间的有效兼顾。
Smart Images

Figure CN122992071A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a cathode material, its preparation method, and its application. Background Technology
[0002] Lithium iron phosphate (LiFePO4) cathode materials have been widely used in power batteries and energy storage systems due to their excellent safety performance, good cycle stability, and abundant raw material sources. However, overcharging remains a significant safety hazard for lithium iron phosphate batteries. During overcharging, a series of side reactions occur inside the battery, such as electrolyte decomposition and damage to the cathode material structure, leading to a rapid rise in temperature. In severe cases, this can cause thermal runaway or even fire and explosion. Therefore, improving the overcharge safety protection capability while ensuring normal battery performance has become a core technical problem that urgently needs to be solved in this field.
[0003] Lithium iron phosphate (LFP) batteries exhibit unique gas generation characteristics under overcharge conditions. Within the normal operating voltage range (2.5V to 3.65V), the LFP material structure remains stable, producing almost no gas. However, when the voltage rises to a higher level (approximately 4.5V), excessive delithiation of the cathode material occurs, leading to changes in the crystal structure. Simultaneously, the electrolyte undergoes oxidative decomposition under high voltage, generating gases such as carbon dioxide and carbon monoxide. Theoretically, the generation of these gases should increase the internal pressure of the cell, prompting the explosion-proof valve to open, thereby achieving safety protection.
[0004] To address this characteristic, existing technologies have proposed several targeted overcharge protection designs for lithium iron phosphate batteries. For example, Chinese patent application 201610269179.X discloses a positive electrode and a lithium-ion battery. Its technical solution involves setting an overcharge protection coating between the positive electrode current collector and the active material layer, or on top of the active material layer. This coating contains an activator and a gas-generating agent. The activator is a material with a specific capacity lower than that of the positive electrode active material. Its characteristic of a sharp voltage increase at the end of charging is used to stimulate the decomposition of the gas-generating agent, thereby causing the explosion-proof valve to activate in response to the gas generation, achieving a short circuit or open circuit between the cell and the external circuit.
[0005] However, the above-mentioned scheme still has some shortcomings in practical applications. First, the gas generation triggering of this scheme depends on the voltage rise of the activator at the end of charging. The gas-generating agent needs to complete the intermediate step of delithiation of the activator to respond to gas generation, which has an inherent delay. During the brief process of voltage surge and activator activation of gas generation, the internal temperature of the battery may have risen sharply, affecting the timeliness of safety protection. Second, the independently set overcharge protection coating, whether located between the current collector and the active material layer or on top of the active material layer, will increase the interfacial impedance of electron and lithium-ion transport, which will adversely affect the rate performance and energy density of the battery.
[0006] Therefore, there is an urgent need for a novel lithium iron phosphate cathode material design scheme that can omit the excitation process and avoid introducing the interfacial impedance of the macroscopic coating, and achieve rapid and controllable voltage-triggered gas generation under overcharge conditions, so that the gas can accumulate rapidly and trigger the explosion-proof valve to start safety protection before rising to a dangerous level, thereby taking into account both the conventional electrochemical performance of the battery and the overcharge safety requirements. Summary of the Invention
[0007] To address the aforementioned issues, this invention provides a cathode material, its preparation method, and its application. The cathode material directly constructs a voltage-sensitive material as an intermediate layer coating the surface of the lithium iron phosphate core, and uses a porous structure composed of fast ion conductor material as the outer shell layer. This eliminates the excitation process and avoids introducing interfacial impedance of the macroscopic coating. Under overcharge conditions, it achieves rapid and controllable voltage-triggered gas generation, allowing the gas to accumulate quickly and trigger the explosion-proof valve to activate safety protection before rising to a dangerous level. This effectively balances the conventional electrochemical performance of the battery with overcharge safety.
[0008] To achieve the above-mentioned objectives, the present invention is implemented through the following technical solution:
[0009] In a first aspect, the present invention provides a cathode material, which is a core-shell structured particle, wherein the core-shell structured particle comprises, from the inside to the outside, a core layer, an intermediate layer covering the outer surface of the core layer, and an outer shell layer covering the outer surface of the intermediate layer; the core layer comprises lithium iron phosphate; the intermediate layer comprises a voltage-sensitive material, wherein the voltage-sensitive material, relative to Li… + / Li undergoes an oxidation reaction and releases gas at an oxidation initiation potential of 4.4~4.6V; the outer shell is a porous layer composed of a fast ion conductor material.
[0010] The oxidation onset potential refers to the potential value at which the response current of the voltage-sensitive material first significantly deviates from the baseline background during the oxidation reaction. The oxidation onset potential is determined using linear sweep voltammetry (LSV), a method well-known in the art. The specific test system and parameters can be determined by those skilled in the art using conventional electrochemical testing methods (such as a conventional three-electrode system and a lithium-based reference electrode).
[0011] Directly coating voltage-sensitive materials onto the surface of lithium iron phosphate particles is not a conventional choice in this field. Such a close-contact structure brings several obvious risks: after the gas-generating agent, as an intermediate layer, undergoes oxidative decomposition under high voltage, its solid residues may contaminate the core active interface, corrode the current collector, and consume the electrolyte, ultimately affecting the battery cycle life. To avoid the aforementioned problems, this invention utilizes a porous fast-ion conductor structure in the outer shell to construct a microscopic control system: the solid-solid interface between the core and the intermediate layer enables the overcharge potential to be instantaneously conducted and directly trigger the oxidation gas generation reaction, eliminating the delayed stage of indirect activation by the activator; simultaneously, the outer shell undertakes the dual responsibility of ion transport and product sieving at the microscale, its fast-ion conductor lattice providing an efficient transport channel for lithium ions to ensure that normal electrochemical performance is not affected, while the nanopores extending to the outer surface allow gas molecules generated in the intermediate layer to quickly escape into the electrolyte to rapidly build up pressure and trigger the safety device. In addition, this porous network system, while ensuring the smooth discharge of gas, can trap the solid residues generated by decomposition in the core region, preventing them from contacting and contaminating the electrolyte or active interface, thus meeting the dual requirements of conventional electrochemical performance and overcharge safety of the battery.
[0012] Preferably, the voltage-sensitive material includes at least one of a conductive polymer, a transition metal salt, and an organic carbonate compound.
[0013] More preferably, the conductive polymer includes at least one of polyaniline, polypyrrole, and polythiophene.
[0014] More preferably, the transition metal salt includes a complex of lithium nitrate and manganese dioxide.
[0015] In this invention, based on a comprehensive consideration of the overcharge behavior characteristics of lithium iron phosphate cathode materials and battery safety protection logic, the oxidation initiation potential of the ideal gas-generating agent must fall precisely within a narrow and safe window. The lower limit of this window must be strictly higher than the highest operating potential of lithium iron phosphate under normal charge / discharge and slight overcharge conditions to ensure that the gas-generating agent maintains chemical inertness and structural stability within the normal battery cycle and allowable voltage fluctuation range, preventing accidental gas generation and ensuring that the normal capacity and cycle life of the battery are not affected. The upper limit of this window must be strictly lower than the dangerous potential of severe electrolyte oxidation and decomposition and irreversible collapse of the lithium iron phosphate crystal structure, ensuring that the gas generation reaction has started and released sufficient gas before the internal temperature of the battery rises sharply to the thermal runaway critical point, thereby triggering the explosion-proof valve to open and cut off the current circuit before the thermal hazard forms.
[0016] To meet the above requirements, this invention screens suitable voltage-sensitive materials from conductive polymers, transition metal salts, and organic carbonate compounds. Taking conductive polymers as an example, materials such as polyaniline undergo peroxidation and breakage of the main chain near 4.5V, releasing small molecule gases (such as CO2 and NO). x The oxidation potentials of these materials fall precisely within the required safety window. For example, lithium nitrate and ethylene carbonate exhibit clear oxidative decomposition and gas production (NO2, CO2, and O2) behavior within this potential range. Although these materials belong to different chemical categories, they share a key function: they can coexist with lithium iron phosphate at normal operating potentials without any side reactions, and when the overcharge potential exceeds a threshold between 4.4 and 4.6V, they can be directly triggered by voltage to rapidly oxidize and decompose, releasing gas without relying on any intermediate excitation process. This directly transforms the overcharge danger signal into a physical pressure signal sufficient to trigger mechanical safety devices, achieving precise control of the safety response in both time and space dimensions.
[0017] Preferably, the fast ion conductor material includes at least one of lithium phosphate, lithium zirconate, lithium lanthanum titanium oxide, and lithium lanthanum zirconium oxide.
[0018] Preferably, the thickness of the outer shell layer is 10~200nm.
[0019] When the thickness is less than 10 nm, the coating layer prepared by atomic layer deposition or sol-gel method is prone to pinholes or incomplete local coverage, failing to form effective physical isolation for the intermediate layer. This leads to the gradual consumption of voltage-sensitive materials due to contact with the electrolyte during normal cycling. The upper limit of 200 nm is mainly limited by lithium-ion transport efficiency. Although fast ion conductor materials have high ionic conductivity, excessively thick coating layers will significantly prolong the solid-phase diffusion path of lithium ions, increase the polarization resistance of the battery, and thus affect the rate performance and capacity utilization of the material.
[0020] Preferably, the porosity of the outer shell layer is 20-50%.
[0021] When the porosity is below 20%, the number of through-channels is insufficient to support the rapid release of the large amount of gas generated by the intermediate layer after overcharging. The gas will accumulate at the core-shell interface, creating pressure that may cause local bulging or even rupture of the outer shell layer, while also hindering the subsequent gas discharge. When the porosity is above 50%, the continuity and density of the outer shell layer will decrease significantly. On the one hand, this will weaken its ability to seal and isolate the solid decomposition residues of the intermediate layer. On the other hand, excessively high porosity will reduce the effective ionic conductivity cross-sectional area of the outer shell layer, which will affect the normal transport of lithium ions. Furthermore, the electrolyte will more easily penetrate through the pores and come into contact with the intermediate layer, causing the intermediate layer to be slowly consumed at the normal operating potential, thus damaging the long-term cycle life of the battery.
[0022] Preferably, the core layer can be lithium iron phosphate or carbon-coated lithium iron phosphate.
[0023] Secondly, the present invention also provides a method for preparing the cathode material as described above, comprising the following steps:
[0024] Provide lithium iron phosphate core materials;
[0025] An intermediate layer is formed on the surface of the lithium iron phosphate core material, the intermediate layer including a voltage-sensitive material, which undergoes an oxidation reaction and releases gas when the oxidation initiation potential relative to Li⁺ / Li is 4.4~4.6V;
[0026] An outer shell layer is formed on the surface of the intermediate layer. The outer shell layer is a porous layer made of fast ion conductor material to obtain the positive electrode material.
[0027] Preferably, the method for forming the intermediate layer includes solution coating or solid-phase adsorption.
[0028] More preferably, the solution coating method includes: dissolving or dispersing a conductive polymer and / or an organic carbonate compound in a solvent to form a coating solution; adding the lithium iron phosphate core material to the coating solution and stirring to mix; and drying the resulting mixture to obtain an intermediate layer coating material.
[0029] More preferably, the solid-phase adsorption method includes: grinding a transition metal salt into nanoparticles; dispersing the lithium iron phosphate core material in a solvent, adding the nanoparticles, and mixing; filtering and drying the resulting mixture to obtain an intermediate layer coating material.
[0030] Preferably, the method for forming the outer shell layer includes atomic layer deposition or sol-gel method.
[0031] More preferably, the atomic layer deposition method uses trimethyl phosphate and lithium tert-butoxide as precursors to deposit a lithium phosphate shell layer on the surface of the intermediate layer coating material, and the deposition temperature is 150~250℃.
[0032] More preferably, the sol-gel method includes: dissolving a zirconium source and a lithium source in a solvent, adjusting the pH value to form a sol; immersing the intermediate coating material in the sol, pulling it out and drying it; and calcining it at 400~600℃ to form a lithium zirconate outer shell layer.
[0033] Thirdly, the present invention provides a positive electrode sheet, including a current collector and a positive electrode material layer disposed on the current collector, the positive electrode material layer comprising the positive electrode material described in any of the first aspects above.
[0034] Fourthly, the present invention provides a lithium-ion battery comprising the positive electrode sheet described in the third aspect above.
[0035] The beneficial effects of this invention are as follows:
[0036] This invention constructs a voltage-sensitive material directly as an intermediate layer coating the surface of the lithium iron phosphate core, directly triggering oxidation and gas generation by overcharge voltage. This eliminates the intermediate step of relying on an activator to induce gas generation, as is done in existing solutions, fundamentally eliminating the inherent delay in gas generation response. This allows gas to accumulate rapidly and trigger the explosion-proof valve before the battery temperature rises sharply to a dangerous level, significantly improving the timeliness and reliability of overcharge safety protection. Simultaneously, the outer shell layer uses a porous structure made of fast-ion conductor material, ensuring normal lithium-ion transport and smooth gas release while effectively isolating the intermediate layer from the electrolyte. This avoids adverse effects on battery rate performance and cycle life, thus achieving an effective balance between conventional electrochemical performance and overcharge safety. Attached Figure Description
[0037] Figure 1 This is a schematic diagram of the microstructure of the core-shell structure of the present invention;
[0038] Figure 2 This is a schematic diagram illustrating the principle of the voltage-triggered gas generation mechanism of the present invention;
[0039] Figure 3 The voltage-gas production characteristic curves are for Example 1 and Comparative Example 1. Detailed Implementation
[0040] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.
[0041] Example 1
[0042] (1) Provide core material: commercial lithium iron phosphate powder with a particle size of 1~5μm is selected.
[0043] (2) Formation of a voltage-sensitive interlayer: A solution coating method was used. 0.5 g of polyaniline was dissolved in 50 mL of N-methylpyrrolidone, and 1.0 g of ethylene carbonate was added. The mixture was stirred to form a homogeneous solution. 10 g of the above-mentioned lithium iron phosphate powder was added to the solution, and the mixture was stirred continuously at 50 °C for 4 hours to ensure that the solution uniformly coated the surface of the lithium iron phosphate particles. The mixture was then dried in a vacuum drying oven at 80 °C for 12 hours to obtain a composite material with an interlayer coating. The voltage-sensitive material used in the interlayer was tested by linear sweep voltammetry, and the oxidation initiation potential relative to Li⁺ / Li was approximately 4.5 V.
[0044] (3) Formation of the outer shell layer: Atomic layer deposition was used, with the above-mentioned intermediate layer coating material as the substrate and trimethyl phosphate and lithium tert-butoxide as precursors. The deposition temperature was 200℃ and the number of cycles was 150 to form a lithium phosphate outer shell layer with a thickness of about 80nm. By controlling the deposition parameters and subsequent processing, the porosity of the outer shell layer was made to be about 30%.
[0045] (4) The resulting product is a core-shell structured cathode material, which consists of a lithium iron phosphate core, a polyaniline-ethylene carbonate composite intermediate layer, and a porous lithium phosphate outer shell. The voltage-sensitive material used in the intermediate layer undergoes an oxidation reaction and releases gas when the oxidation potential relative to Li⁺ / Li is approximately 4.5V.
[0046] Example 2
[0047] (1) Provide core material: Select carbon-coated lithium iron phosphate powder with a particle size of 2~8μm.
[0048] (2) Formation of a voltage-sensitive intermediate layer: Solid-phase adsorption method was used. Lithium nitrate and manganese dioxide were mixed in a molar ratio of 1:1 and ground into nanoparticles with a particle size of approximately 50-100 nm. 10 g of the above carbon-coated lithium iron phosphate powder was dispersed in 100 mL of anhydrous ethanol, and 2 g of the above nanoparticles were added. After ultrasonic dispersion for 30 minutes, mechanical stirring was continued for 2 hours to ensure that the nanoparticles were uniformly adsorbed on the surface of lithium iron phosphate. After filtration, the mixture was vacuum dried at 60 °C for 6 hours to obtain the composite material with an intermediate layer. The oxidation initiation potential of the voltage-sensitive material used in this intermediate layer relative to Li⁺ / Li was approximately 4.6 V, as determined by linear sweep voltammetry.
[0049] (3) Formation of the outer shell layer: The sol-gel method was used. Tetrabutyl zirconate was dissolved in ethanol, and lithium acetate aqueous solution was added to adjust the pH value to 8-9 to form a transparent sol. The above intermediate coating material was immersed in the sol, slowly pulled out and dried. The immersion-pulling-drying process was repeated 3 times. Then, it was calcined at 500°C for 2 hours to form a lithium zirconate outer shell layer with a thickness of about 60 nm and a porosity of about 40%.
[0050] (4) The resulting product is a core-shell structured cathode material, which consists of a carbon-coated lithium iron phosphate core, a lithium nitrate-manganese dioxide composite intermediate layer, and a porous lithium zirconate outer shell. The voltage-sensitive material used in the intermediate layer undergoes an oxidation reaction and releases gas at an oxidation potential of approximately 4.6V relative to Li⁺ / Li.
[0051] Comparative Example 1
[0052] This comparative example directly uses the commercial lithium iron phosphate powder used in Example 1 as the positive electrode material without any coating treatment, and the particle size is 1~5μm.
[0053] Performance testing
[0054] The positive electrode materials obtained in Examples 1-2 and Comparative Example 1 were mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 8:1:1, respectively, and coated onto aluminum foil current collectors to form positive electrode sheets. Using lithium metal sheets as negative electrodes, 1M LiPF6 / EC:DMC:EMC (volume ratio 1:1:1) as the electrolyte, and a Celgard separator, CR2032 coin cells were assembled.
[0055] The gas generation mechanism of the cathode material provided by this invention is as follows: Figure 2 As shown. Figure 2 The diagram illustrates, at the microscopic scale, the operating states of a single core-shell structured particle under different voltage conditions, where... Figure 2 (a) is the normal operating state (2.5V~3.65V). Figure 2 (b) indicates an overcharge state (greater than 4.5V). Under normal operating conditions, such as... Figure 2As shown in (a), lithium ions can be smoothly transported through the fast-ion conductor lattice channels of the outer shell layer to complete the normal electrochemical charge-discharge process; at the same time, the voltage-sensitive material in the middle layer is in a chemically inert state and does not undergo any oxidation or decomposition reaction, and the entire core-shell structure particles only perform the energy storage function. When the battery is overcharged and the voltage rises above 4.5V, as... Figure 2 As shown in (b), its surface potential rises sharply, directly acting on the adjacent voltage-sensitive intermediate layer, triggering an oxidation reaction and rapid decomposition to release gas molecules. The generated gas molecules pass through the nano-perforated pores of the outer shell layer and are released outward into the electrolyte, rapidly accumulating pressure inside the cell to trigger the safety protection device. During this process, the outer shell layer continuously plays an isolating role, confining the solid residues generated by the decomposition of the intermediate layer to the core region and preventing them from contacting the electrolyte.
[0056] An overcharge safety test was performed on it, and the test results are as follows: Figure 3 As shown. The battery was charged to 5.0V at a constant current of 0.5C, and the battery state was observed and the gas generation behavior was recorded. The gas generation behaviors of Example 1 and Example 2 were similar. For ease of analysis, the voltage-gas generation characteristics of Example 1 and Comparative Example 1 were compared. The comparison graph is shown below. Figure 3 As shown in the figure, the core-shell structure cathode material provided in Example 1 produces almost no gas within the normal operating voltage range below 4.5V. However, once the voltage exceeds the trigger point of 4.5V, the gas production rate increases sharply, and the gas production rate during the rapid gas production phase is much higher than that of the traditional lithium iron phosphate material in Comparative Example 1. This characteristic enables the material of the present invention to rapidly accumulate gas pressure and trigger the explosion-proof valve to open before the internal temperature of the battery rises sharply to a dangerous level, thus achieving active safety protection.
Claims
1. A positive electrode material, characterized in that, It is a core-shell structured particle, which, from the inside out, comprises a core layer, an intermediate layer covering the outer surface of the core layer, and an outer shell layer covering the outer surface of the intermediate layer; the core layer comprises lithium iron phosphate; the intermediate layer comprises a voltage-sensitive material, the voltage-sensitive material being sensitive to lithium iron phosphate. + / Li undergoes an oxidation reaction and releases gas at an oxidation initiation potential of 4.4~4.6V; the outer shell is a porous layer composed of a fast ion conductor material.
2. The cathode material according to claim 1, characterized in that, The voltage-sensitive material includes at least one of conductive polymers, transition metal salts, and organic carbonate compounds.
3. The cathode material according to claim 2, characterized in that, The conductive polymer includes at least one of polyaniline, polypyrrole, and polythiophene.
4. The cathode material according to claim 2, characterized in that, The transition metal salts include complexes of lithium nitrate and manganese dioxide.
5. The positive electrode material according to claim 1, characterized in that, The fast ion conductor material includes at least one of lithium phosphate, lithium zirconate, lithium lanthanum titanium oxide, and lithium lanthanum zirconium oxide.
6. The cathode material according to claim 1, characterized in that, The thickness of the outer shell layer is 10~200nm.
7. The cathode material according to claim 1, characterized in that, The porosity of the outer shell layer is 20-50%.
8. A method for preparing a positive electrode material as described in any one of claims 1-7, characterized in that, Includes the following steps: Provide lithium iron phosphate core materials; An intermediate layer is formed on the surface of the lithium iron phosphate core material, the intermediate layer including a voltage-sensitive material, which undergoes an oxidation reaction and releases gas when the oxidation initiation potential relative to Li+ / Li is 4.4~4.6V; An outer shell layer is formed on the surface of the intermediate layer. The outer shell layer is a porous layer made of fast ion conductor material to obtain the positive electrode material.
9. A positive electrode sheet, characterized in that, It includes a current collector and a positive electrode material layer disposed on the current collector, the positive electrode material layer comprising the positive electrode material according to any one of claims 1-7.
10. A lithium-ion battery, characterized in that, Includes the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
A positive electrode and a lithium-ion battery
CN105810885B